The Effect of Government Expenditure and Economic Growth on Gender Development Index in Special Region of Yogyakarta Province - Silvina Esta Nurwanti; Nunik Kadarwati; Supadi Supadi; Khalid Eltayeb Elfaki Adam (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2021)
The phenomenon of the development inequality between men and women is development problems that still occur in many regions and can be measured using gender development index. This research has purpose to analyze the factors that influence on gender development index in Special Region of Yogyakarta and indentifying variables that has most influence on gender development index in Special Region of Yogyakarta. This research uses gender development index as dependent variable and was implemented in the Province of D.I. Yogyakarta, in contrast to the previous research that already exists. In this research, the author have a hypothesis formulation that all independent variables, government expenditure in education sector, government expenditure in health sector and economic growth has a positive effect on gender development index. This research uses a panel data regression analysis with fixed effect model (FEM) approach. The results of this research indicate that variable of government expenditures in education has a negative and significant effect on gender development index in Province of D.I. Yogyakarta, the variable of government expenditures in health and variable of economic growth has a positive and significant effect on gender development index in Province D.I. Yogyakarta, and the dependent variable has most influence on gender development index in Special Region of Yogyakarta is a government expenditure on health. The implication of this research is the government to pay more attention to ability of each region in realizing the education expenditure, it is neccesary to strengthen cooperaton and equalize of mission both at the province and district/city level to optimize government performance, and need equality on education to reduce education gap in Special Region of Yogyakarta. For expenditure in the health sector, government should increase the percentage of budget allocation for health sector with provision minimum of 10 percent from local government revenue and expenditure budget (APBD) and need performance optimization in financial management so that health budget can be realized optimally as well. Meanwhile in economic growth, the government should to make equalize in the economic growth for each district or city so that can be enjoyed by all level of society. The limitations of this study are use of research data with a limited period and limited information on availability of information on each research variable used